FIAT MONEY DALAM PERSPEKTIF EKONOMI DAN HUKUM ISLAM - Ummi Kalsum (Al 'Adalah: Jurnal Hukum Islam, 2017)
Abstract: Fiat Money in Perspective Economics and Islamic Law. There is a difference of opinion among jurists in the legal status of fiat money that is practiced today. Some scholars assert that the currency should be based on gold and silver or monetary standard should be gold and silver, which is determined based on syar’i. Thus, the fiat money system adopted today in Islam should not be. This opinion was an inspiration for contemporary Islamic economic thinkers who initiated the return of the application of gold-based currency and silver (dinars and dirhams). Opinion of some other scholars, support the permissibility of use currencies other than the dinar and dirham as defined not by Shar’ie but based on the ‘urf. To minimize the economic impact of fiat money, the expected use of foreign currency reduced to a minimum. Keywords: fiat money, Islamic law, Islamic economics